Diversity within diversity management : types of diversity in organizations - Georgiadou, Andri; Gonzalez-Perez, Maria Alejandra; Olivas-Lujan, Miguel R. (Advanced series in management, 2019)
Managing diversity plays a crucial part in enabling every member of the workforce to perform up to their full potential. Managers demand satisfactory performance from every member of their workforce and expect the best of their employees. But often, diversity and its management are not viewed as clear contributors to the organization's performance and bottom-line. Managing and leveraging diversity are set aside from the rest of the organization and hence, they are often undervalued amid all the other barriers that companies face. Whilst there is no single tried-and-tested "solution" to diversity and no easy way to manage implementation barriers, this edited collection of case studies from around the globe provides new insights for practitioners, managers, students and researchers. The book seeks to shed light on existing practices disseminating the value of diversity, whilst opening the road toward a wider perspective on its definitions. The contributors provide critical reflections of the current discourse on different types of diversity in heterogenous organizations around the world.